2017
DOI: 10.3748/wjg.v23.i14.2511
|View full text |Cite
|
Sign up to set email alerts
|

Berberine displays antitumor activity in esophageal cancer cellsin vitro

Abstract: AIMTo investigate the effects of berberine on esophageal cancer (EC) cells and its molecular mechanisms.METHODSHuman esophageal squamous cell carcinoma cell line KYSE-70 and esophageal adenocarcinoma cell line SKGT4 were used. The effects of berberine on cell proliferation were evaluated using the 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. For cell cycle progression, KYSE-70 cells were stained with propidium iodide (PI) staining buffer (10 mg/mL PI and 100 mg/mL RNase A) for 30 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(42 citation statements)
references
References 23 publications
(31 reference statements)
0
42
0
Order By: Relevance
“…Berberine has diverse pharmacological effects and is normally used for the treatment of gastroenteritis [133,134]. It exhibits significant anti-cancer effects in a wide spectrum of cancers including ovarian, breast, esophageal, and thyroid cancers, leukemia, multiple myeloma, nasopharyngeal carcinoma, and neuroblastoma, through inducing cell cycle arrest and apoptosis, inhibiting metastasis and angiogenesis [135][136][137][138][139][140][141][142][143].…”
Section: Berberinementioning
confidence: 99%
“…Berberine has diverse pharmacological effects and is normally used for the treatment of gastroenteritis [133,134]. It exhibits significant anti-cancer effects in a wide spectrum of cancers including ovarian, breast, esophageal, and thyroid cancers, leukemia, multiple myeloma, nasopharyngeal carcinoma, and neuroblastoma, through inducing cell cycle arrest and apoptosis, inhibiting metastasis and angiogenesis [135][136][137][138][139][140][141][142][143].…”
Section: Berberinementioning
confidence: 99%
“…Berberine has extensive pharmacological effects, including anti-hypertensive, anti-diabetic, anti-arrhythmia and anti-hyperlipidemic (3)(4)(5)(6). Recent studies have shown that berberine exerts antitumor effects in a variety of human cancer cells, such as breast cancer, hepatocellular carcinoma, leukemia, and esophageal cancer, both in vitro and in vivo, by suppressing proliferation, inducing apoptosis, arresting the cell cycle, and inhibiting invasion and metastasis (7)(8)(9)(10)(11)(12). In addition, it has been recently reported that berberine-induced autophagy has been observed in hepatic and colon cancer cells (13,14).…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, many studies have shown that BBR can be used for treating hypertension, cardiovascular diseases (due to antiheart failure, antiarrhythmia, and antiplatelet aggregation effects), neuronal diseases, gastrointestinal disorders, and several types of cancers [6][7][8][9][10]. e molecular and cellular mechanisms underlying the therapeutic effects of BBR, such as anti-inflammatory, antiapoptotic, antioxidative, and autophagy-promoting activities, have been found to involve some signaling pathways, such as the mitogen-activated protein kinase (MAPK) signaling, phosphatidylinositol-3 kinase/AKT/mammalian target of rapamycin (PI3K/Akt/mTOR), the Janus Kinase 2/signal transducer and activator of transcription 3 (JAK2/STAT3), and the nuclear factor erythroid 2-related factor 2/hemeoxygenase-1 (Nrf2/HO-1) pathways [11].…”
Section: Sources and Pharmacological Effects Of Berberine (Bbr)mentioning
confidence: 99%